La scrittura femminile e l’infinito di Dio (Materiali di Estetica. Terza serie, 2019)
This paper provides some examples of women’s writing in dialogue with God. A premise of the text is that “God” is a word alluding to the opening up of the impossible into necessity. The women’s texts selected are Etty Hillesum’ Diary and Caterina da Siena’s Dialogue, followed by Antonietta Potente’s discourse as a commentary on the Gospel of Thomas. From these three examples, the centrality of the infinite emerges as an opening moment within historical time. The infinite is presented as belonging to the experimental experience accompanied by the discourse. The reference to experimental experience and discourse, never fully complete and harmonious, is indicated as being characteristic of this genre of women’s writing.